2021
DOI: 10.1101/2021.04.13.439583
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Data-driven and interpretable machine-learning modeling to explore the fine-scale environmental determinants of malaria vectors biting rates in rural Burkina Faso

Abstract: Background: Improving the knowledge and understanding of the environmental determinants of malaria vectors abundances at fine spatiotemporal scales is essential to design locally tailored vector control intervention. This work aimed at exploring the environmental tenets of human-biting activity in the main malaria vectors (Anopheles gambiae s.s., Anopheles coluzzii and Anopheles funestus) in the health district of Diebougou, rural Burkina Faso. Methods: Anopheles human-biting activity was monitored in 27 villa… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 89 publications
(96 reference statements)
0
4
0
Order By: Relevance
“…Of these, 24/29 (82.8%) actually shared code, 29/33 (87.9%) actually shared data and 5/6 (83.3%) were indeed registered. The papers that used registration were two malaria models(14,15), one vector model (16) (which focused on malaria vectors) one polio (Sabin 2 virus (17)) model and one rotavirus model(18). The majority were from 2021(14,16,17) and were also malaria models (two malaria and one vector that was essentially malaria (1416)) the majority we also classified as spatiotemporal (1416).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Of these, 24/29 (82.8%) actually shared code, 29/33 (87.9%) actually shared data and 5/6 (83.3%) were indeed registered. The papers that used registration were two malaria models(14,15), one vector model (16) (which focused on malaria vectors) one polio (Sabin 2 virus (17)) model and one rotavirus model(18). The majority were from 2021(14,16,17) and were also malaria models (two malaria and one vector that was essentially malaria (1416)) the majority we also classified as spatiotemporal (1416).…”
Section: Resultsmentioning
confidence: 99%
“…The papers that used registration were two malaria models(14,15), one vector model (16) (which focused on malaria vectors) one polio (Sabin 2 virus (17)) model and one rotavirus model(18). The majority were from 2021(14,16,17) and were also malaria models (two malaria and one vector that was essentially malaria (1416)) the majority we also classified as spatiotemporal (1416). Finally, of the 120 articles (10%) that text mining found that they contained a COI statements, there was indeed a placeholder for this ststement in all articles, but the vast majority of the statements (115 (95.8%)) disclosed no conflict at all.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…LIME has only recently started to be used in environmental and ecological applications (e.g., Cha et al, 2021; Ryo et al, 2021; Taconet et al, 2021).…”
Section: Model Agnostic Explainability Methodsmentioning
confidence: 99%